Pregnancy Complicated by Ludwig's Angina Requiring Delivery - Kathleen Moorhead; Maryam Guiahi (Hindawi Limited, 2010)
At 33 weeks of gestation, a 24-year-old developed Ludwig's angina that worsened despite aggressive therapy. This is the first reported case of Ludwig's Angina in pregnancy that required an emergent cesarean section for fetal indications. Delivery may have contributed to improvement in the mother's health status.